Implementasi Algoritma Greedy pada Pencarian Langkah Optimal Permainan Mahjong Solitaire - Alvin Juvianto; Halim Agung (Ikatan Ahli Informatika Indonesia (IAII), 2017)
The game of mahjong solitaire is a difficult tough teaser and takes a long time to complete when manually played by the user. The greedy algorithm is applied to find the optimal step in completion of this solitaire mahjong game. The algorithm used in this research is greedy algorithm. The result of this research is game of mahjong solitaire with 5 model of tile arrangement where game can be completed manually or automatically by greedy algorithm. The greedy algorithm is applied to compare the acquisition of the most tile pairs in the 1 step forward when 1 pair of tiles is removed. The conclusion of this study is from 250 times testing of 5 levels of the game where the test at each level as much as 50 times, obtained the victory as much as 168 times and defeat as much as 82 times. So the percentage of success of greedy algorima in completion of game of solitaire mahjong is 67.2%. While in manual testing, from 250 times the test of 5 levels of the game where the test at each level as much as 50 times by 5 players, obtained 161 victories and defeat 89 times. So the percentage of success of greedy algorima in game settlement is 64.4%.